2014
DOI: 10.1364/oe.22.015267
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative confocal phase imaging by synthetic optical holography

Abstract: We demonstrate quantitative phase mapping in confocal optical microscopy by applying synthetic optical holography (SOH), a recently introduced method for technically simple and fast phase imaging in scanning optical microscopy. SOH is implemented in a confocal microscope by simply adding a linearly moving reference mirror to the microscope setup, which generates a synthetic reference wave analogous to the plane reference wave of wide-field off-axis holography. We demonstrate that SOH confocal microscopy allows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 22 publications
0
33
0
Order By: Relevance
“…It was demonstrated that SOH is a method technically simple and fast for phase imaging. 9,10 It can be integrated in scanning microscopes by simply adding a linearly moving reference mirror, which generates a synthetic reference wave, analogous to the plane reference wave of wide-field off-axis holography. The present work describes a synthetic holography system, implemented through a lens-free microscope based on a low-coherence scanning optical micro-cavity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that SOH is a method technically simple and fast for phase imaging. 9,10 It can be integrated in scanning microscopes by simply adding a linearly moving reference mirror, which generates a synthetic reference wave, analogous to the plane reference wave of wide-field off-axis holography. The present work describes a synthetic holography system, implemented through a lens-free microscope based on a low-coherence scanning optical micro-cavity.…”
mentioning
confidence: 99%
“…The direct term U S was filtered, demodulated and subsequently an inverse FT was performed. In image recovering, we exploit only the term of first order appearing in Equation (9), neglecting the higher orders that are strongly attenuated. The above results confirm the potentialities of this technique in realizing imaging at multi-wavelengths with just one scan.…”
mentioning
confidence: 99%
“…The second way is introduced by moving the reference arm. Although this method has been applied to SOH and Fourier-Domain optical coherence tomography [11,19], application of it into the LCHM yields a high-speed en-face complex confocal imaging technique. Using a custom axial height phantom fabricated using chrome deposition, we have demonstrated that both off-axis and in-line LCHMs yielded variations in phase corresponding to heights in the ~100 nm range with a contrast-to-noise ratio of ~31 dB.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore it is limited to static samples. In 2014, synthetic optical holography (SOH) was proposed to achieve quantitative confocal phase imaging by moving a reference mirror to introduce a spatial frequency carrier [11]. SOH realized one single-shot hologram for one en-face confocal image thereby reducing the data flow by 6 orders of magnitude compared to DCM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation